Graduate employability and preparedness: a case study of University of Malaysia Perlis (UNIMAP), Malaysia - Nooriah Yusof; Zakiyah Jamaluddin (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Graduate employability and unemployment are issues that have given rise to many policy implications for higher education in many developing countries such as Malaysia. The employability of graduates depends on individual factors, the labour market and organizational practices. Individual factors refer to the graduate’s proactive attitude and behaviours with respect to the desired career opportunities. This study examined the nature of Malaysia’s undergraduate proactive actions in employment preparedness prior to entering the job market. The actions evaluated pertained to the employability potentials of 171 Universiti Malaysia Perlis (UniMAP) final year engineering undergraduate respondents as demanded by the market upon leaving the education system. The primary data were gathered from questionnaire surveys. Results showed that several forms of proactive actions taken by the undergraduates fell short of the clear and focused planning and strategy essential to fulfil the market needs of their potential careers upon finishing study. Thus interventions at University level for the students are crucial to enhance their employability.